Studi Pemupukan Fosfat Terhadap Viabilitas Dan Vigor Benih Jagung (Zea mays L.) Varietas Hulaliu - M. K Lesilolo (Faculty of Agriculture, Pattimura University, 2012)
This study aimed to determine the best level of phosphate basic fertilization for seed production of Hulaliu corn varieties with high viability and vigor. This study was conducted in two places, namely in Booi Village, Saparua Subdistrict, Central Maluku District, for experiment with phosphate fertilization treatment, and in the Laboratory of Balai Besar Perbenihan dan Proteksi Tanaman Perkebunan Maluku in Passo, Baguala Subdistrict, Ambon, for testing seed viability and vigor. The experimental design used was a single factor Randomized Block Design with five levels of phosphate fertilization, consisting of P1 = 50 kg P2O5 per ha; P2 = 55 kg P2O5 per ha;. P3 = 60 kg P2O5 per ha; P4 = 65 kg P2O5 per ha, P5 = 70 kg P2O5 per ha = 70 kg, and with three replications. The results showed that the optimal levels of phosphate fertilization to enhance seed viability and vigor of Hulaliu local corn varieties were between 55 to 70 kg P2O5 per ha.